Efektivitas Penggunaan E-Commerce Sebagai Penunjang Aktivitas Bisnis pada Usaha Kecil Menengah (UKM) di Malang Raya - Sri Palupi Prabandari; Misbahuddin Azzuhri (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2011)
Nowadays the business experienced good growth in Malang Territory. This is shown from many new companies raise up. In other side, driven by rapid development of information and communication technologies and globalization of business, e?commerce is becoming increasingly important in many organizations. E-commerce provide convenience to the company to introduce products, dealing with customers and suppliers. However, not many companies that use e-commerce for several reasons. These problems are examined in this study. This study was used qualitative descriptive analysis to examine SMEs e-commerce practices in Malang Territory. This paper presents the findings of an empirical study conducted to investigate the use of e?commerce by SMEs in Malang Territory. The interviews with owners/managers of 41 SME’s operating in Malang Territory shows that size and age of a firm plays a vital role in e?commerce adoption. It also outlines the common barriers to implement e?commerce by SMEs. Implications to the policy makers are also highlighted.Keywords: effectivity, e-commerce, SMEs, qualitative descriptive